Genetic Alteration Profiling of Chinese Lung Adenocarcinoma and Its Effect on Targeted Therapy Efficacy - Liu, Jie; Xu, Wang-yang; Ye, Maosong; Liu, Zilong; Li, Chun (Frontiers in Oncology, 2021)
Background: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer and a highly heterogeneous disease with a diversity of phenotypes and genotypes in different populations. The purpose of this study is to investigate oncogenic genetic alterations on lung adenocarcinoma (LUAD) in eastern China and their significance in targeted therapy. Methods: This study enrolled 101 LUAD patients and used a customized 639 genes DNA panel to detect molecular alterations of the tumor. Comprehensive analysis of mutations and clinical application of genomic profiling was carried out. Results: The most commonly mutated genes were epidermal growth factor receptor (EGFR) (53%) and tumor protein p53 (TP53) (32%). The less frequently mutated genes were erb-b2 receptor tyrosine kinase 2 (ERBB2) (25%), ATR serine/threonine kinase (ATR) (20%), CCAAT enhancer binding protein alpha (CEBPA) (16%), RB transcriptional corepressor 1 (RB1) (16%), transcription factor 7 like 2 (TCF7L2) (14%), ROS proto-oncogene 1, receptor tyrosine kinase (ROS1) (12%) and spectrin alpha, erythrocytic 1 (SPTA1) (12%). Among them, the frequency of ERBB2, ATR, CEBPA, RB1 and TCF7L2 mutations was much higher than that in the databases. Seventy percent of the patients harbored at least one actionable alteration of targeted therapy according to the OncoKB evidence. CEBPA mutations affected the response to EGFR-tyrosine kinase inhibitors. ERBB2, CEBPA and TCF7L2 mutated tumors were significantly associated with high tumor mutation burden (TMB). Conclusions: LUAD patients from eastern China have a unique profile of mutations. The targeted DNA panel is helpful for personalized treatment decision of LUAD patients, and the specific mutation patterns may affect the response to targeted therapies.